2020
DOI: 10.1186/s40510-020-00313-9
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal growth in class II malocclusion from childhood to adolescence: does the profile straighten?

Abstract: Background: There is relatively little appreciation of the changes in maxillary-mandibular relationships occurring during adolescence among subjects with normal and increased overjet. The aim of this study was to assess differences in changes in maxillo-mandibular relationships during the adolescent growth period based on the presence of a normal (< 4 mm) or increased (> 4 mm) overjet in childhood. Our hypothesis was that there is no difference in the change of the A point, nasion, B point (ANB) angle during g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[12] Research by Ardani et al [13] on Javanese found skeletal class II malocclusion caused by micrognathia mandible. Other research was conducted by Taloumtzi et al [14] In patients aged 8-10 years, it was suggested that skeletal class II malocclusion was due to a prognathic maxilla (25%) and the remainder to a retrognathic mandible (75%). The results of this study are in agreement with the two studies, namely, that the average SNA angle to the cranium base is normal, and the average SNB angle to the cranial base is retrognathic.…”
Section: Discussionmentioning
confidence: 97%
“…[12] Research by Ardani et al [13] on Javanese found skeletal class II malocclusion caused by micrognathia mandible. Other research was conducted by Taloumtzi et al [14] In patients aged 8-10 years, it was suggested that skeletal class II malocclusion was due to a prognathic maxilla (25%) and the remainder to a retrognathic mandible (75%). The results of this study are in agreement with the two studies, namely, that the average SNA angle to the cranium base is normal, and the average SNB angle to the cranial base is retrognathic.…”
Section: Discussionmentioning
confidence: 97%